STUDY OF STRUCTURE AND ACTIVITY MANGANESE SUPEROXIDE DISMUTASE HYBRID STAPHYLOCOCCUS EQUORUM/S. SAPHROPHYTICUS} - Arumsari, Sekar
Superoxide dismutase (SOD) is a component of defense mechanism against reactive oxygen species (ROS), by the reduction of superoxide radical into oxygen and hydrogen peroxide. Previous study showed that a hybrid SOD enzyme S. equorum/S. saphrophiticus (rMnSODSeq) formed a dimer and thermal shift assay results showed this enzyme had two Tm at 52 0C (Tm monomer, TmM) and 680C (Tm dimer, TmD). The aims of research was to study the relationship between structure and activity at a molecular level using thermal shift assay and activity assay based on the ability of SOD to inhibit NBT oxidation by riboflavin. Protein stability against SOD inhibitors, chaotropic and reducing apnts, detergents, NaCl, and UVC exposure was studied. The increase of protem stability against UVC was obtained by protein engineering by substitl@ing Leu] 69Trp. The initial step to determine the three-dimensional structure of rMnSODSeq was obtained through protein crystallization by vapor diffusion method. The results showed that transition dimer to monomer occurred only in the addition of NaN3 inhibitor, 6 M and 4.5 M GdnHCl, I M and 2 M NaCl, and exposure to pH 2 and UVC. Transition dimer-monomer did not occur in the addition of chaotropic agents (urea 6 M), detergents (0.5% SDS and 0.5% Triton X-100), reducing agents (5 mM DTT, 5 mM ß-mercaptoethanol, 5 mM Na2S205), and in pH 3-12. Association of monomer to dimer occurred in temperature reduction from 520C to 37oc in all concentrations of GdnHCl. Protein stability against UVC was increased by Leul 69Trp substitution and was proved by the increase of residual activity from 78% to 98%. Crystal protein rMnSODSpq which diffracted at 2,7Å had been obtained in a condition 3.8 mg/mL protein, 0.02 MgCi2, 0.1 M HEPES pH 7.5, and 25% w/v PEG 3350. Information about the structure and activity relationship of rMnSODSeq obtained from this study can be useful for the development of this enzyme as therapeutic agent in the future,